GROWTH PERFORMANCE AND INTESTINAL Aeromonas spp. OF BONYLIP BARB (Osteochilus vittatus) AFTER RECEIVING DIET CONTAINING SALT AND HERBAL CONCOCTION SUPPLEMENTATION - Syakuri, Hamdan; Soedibya, Petrus Hary Tjahja; Marnani, Sri; Ekasanti, Anandita; Kasprijo, Kasprijo; Kusuma, Rima Oktavia; Wijaya, Rudy; Nugrayani, Dewi; Listiowati, Emyliana; Palupi, Mustika (Agency for Marine and Fisheries Extension and Human Resources, 2024)
Salt and herbal supplementations in fish feed are expected to promote aquaculture productivity, including for slow-growing fish such as Bonylip barb (Osteochilus vittatus). The objective of this study was to evaluate the growth performance and occurrence of Aeromonas spp. in the intestine of Bonylip barb fed a diet supplemented with salt and herbs. This experiment was conducted using a completely randomized design with four treatments: 1) control, 2) salt 3% supplementation, 3) herbal supplementation, and 4) Salt 3% and herbal supplementation. Growth performance evaluation included weight gain, relative growth rate, and specific growth rate after 30 and 60 days of rearing. Bacterial samples were isolated on trypticase soy agar (TSA) and glutamate starch phenol red agar (GSP) media. Yellow colonies on GSP were counted and confirmed as Aeromonas spp. via molecular identification based on 16S rDNA sequence. Results showed that herbal supplementation, either alone or in combination with 3% salt, insignificantly increased the fish growth performance in the short-term (30 days), but tended to decrease it over the long-term (60 days). Salt supplementation consistently decreased fish growth performance but improved fish survival rates. Aeromonas isolates comprised more than 60 % of the culturable intestinal bacteria in all treatments. Furthermore, herbal supplementation appeared to increase the percentage of Aeromonas spp. in the intestine, with identified species including Aeromonas veronii, Aeromonas caviae, and Aeromonas jandaei.